The Market for Seamen in the Age of Sail. - Fischer, Lewis R. (Liverpool University Press, 2017)
This volume collects eight essays that all attempt to answer two key concerns: did markets for seafarers exist in the age of sail; and, if so, were these markets efficient?
The Danish Maritime Labour Market, 1880-1900""
Keywords: Merchant mariners -- Supply and demand -- History.; Merchant marine -- History.; Marins (Marine marchande) -- Offre et demande -- Histoire.; Marine marchande -- Histoire.; Merchant marine; Merchant mariners -- Supply and demand; History